Ways Out of the Patenting Prohibition? Human Parthenogenetic and Induced Pluripotent Stem Cells. (9th February 2017) - Schickl, Hannah; Braun, Matthias; Dabrock, Peter
Abstract: According to the judgement of the European Court of Justice in 2014, human parthenogenetic stem cells are excluded from the patenting prohibition of procedures based on hESC by the European Biopatent Directive, because human parthenotes are not human embryos. This article is based on the thesis that in light of the technological advances in the field of stem cell research, the attribution of the term 'human embryo' to certain entities on a descriptive level as well as the attribution of a normative protection status to certain entities based on the criterion of totipotency, are becoming increasingly unclear. The example of human parthenotes in particular demonstrates that totipotency is not at all a necessary condition for the attribution of the term 'human embryo'. Furthermore, the example of hiPSC and somatic cells particularly shows that totipotency is also not a sufficient condition for the attribution of a normative protection status to certain entities. Therefore, it is not a suitable criterion for distinguishing between human embryos worthy of protection and human non‐embryos not worthy of protection. Consequently, this conclusion has repercussions for the patenting question. The strict delineation between an ethically problematic commercial use of human embryos and the concomitant patenting prohibition of hESC‐based procedures and an ethically unproblematic commercial use of human non‐embryos and the therefore either unrestrictedly permitted (cf. human parthenotes) or even unregulated (cf. hiPSC) patenting of procedures based on these alleged alternatives becomes increasingly blurred.